2022
DOI: 10.3389/fimmu.2022.821818
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Inflammation Might Protect Hemodialysis Patients From Severe COVID-19

Abstract: Hemodialysis patients (HD) are expected to have excess mortality in coronavirus disease 2019 (COVID-19). This was challenged by a recent study reporting HD patients to have comparable mortality and less ICU admissions when hospitalized with COVID-19. An altered immune system due to chronic inflammation might protect HD-patients from severe COVID-19. Therefore, we aimed to describe the peripheral blood immune phenotype in HD-patients and respective controls with COVID-19.MethodsSixty-four patients (31 HD, 33 no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…Some previously published reports showed high mortality rates among maintenance hemodialysis patients hospitalized for SARS-CoV-2 [ 33 36 ]. Some other studies demonstrated that chronic inflammation, a salient feature in HD patients, might protect those patients from severe COVID-19-related symptoms, ICU admission, and mortality [ 9 , 16 ]. These discordant results are accepted because of the limitations known in the observational studies and multiple confounders which can affect the patient prognosis like age [ 37 ], associated comorbidities, and selection bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previously published reports showed high mortality rates among maintenance hemodialysis patients hospitalized for SARS-CoV-2 [ 33 36 ]. Some other studies demonstrated that chronic inflammation, a salient feature in HD patients, might protect those patients from severe COVID-19-related symptoms, ICU admission, and mortality [ 9 , 16 ]. These discordant results are accepted because of the limitations known in the observational studies and multiple confounders which can affect the patient prognosis like age [ 37 ], associated comorbidities, and selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…( www.ncss.com ). Calculation relied upon a previous study that characterized Tregs in HD patients [ 16 ]. Group sample sizes of 30 and 30 achieve 85% power to reject the null hypothesis of zero effect size when the population effect size is 0.8 and the significance level (alpha) is 0.050 using a two-sided two-sample equal-variance t-test.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, GDF-15 emerged as the only biomarker independently associated with poor outcomes in non-dialysis renal patients affected by SARS-CoV-2 infection, out of the other 19 molecules responsive to inflammatory stimuli. Notably, the panel of cytokines, chemokines and uremic toxins that were investigated was built according to the literature review on the more promising biomarkers dysregulated in the course of COVID-19 and/or renal disease [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the use of complex research biomarkers, such as metabolomic analyses ( 12 ) or deep immune phenotyping ( 13 ), is of great interest to understand the pathophysiology of this disease better, especially in vulnerable patient groups, the clinical applicability of such complex biomarkers and scores is currently limited due to lack of availability and high costs. A review of 76 different coring systems, ranging from existing scores to newly developed scores, artificial intelligence algorithms and novel biomarker came to the conclusion that all of these scores have limitations but that the combination of single laboratory parameters may have the greatest potential for implementation ( 14 ).…”
Section: Discussionmentioning
confidence: 99%